ENDOMETRIOSIS - A CRIPPLING ILLNESS: A RARE CASE OF BLADDER ENDOMETRIOMA - Bano, Alia; Anam Riaz; Samina Saleem (Journal of Ayub Medical College Abbottabad, 2021)
Endometriosis is a common gynaecological condition affecting 10-12% of general female population. It has variable clinical presentation commonly causing infertility, chronic pelvic pain, and dysmenorrhea. Rare presentation could be a tender cervical/rectal mass therefore should be considered in women of reproductive age group. A 30 years old woman with 1.5 years history of heavy menstrual bleeding with painful menstruation, painful coitus, urinary hesitancy and constipation reported after visiting multiple hospitals and failed medical treatment with pelvic scans showing fibroid uterus. MRI excluded fibroid uterus and laparoscopic exploration of pelvis and subsequent histopathology confirm the mass to be bladder endometrioma.